“Business Model” and “Monetisation”: On the Uses of Buzzwords - Thomas Streeter (tripleC: Communication, Capitalism & Critique)
This essay explores the function of corporate buzzwords by investigating the early histories of “business model” and “monetisation”. It analyses the terms as examples of managerial argot, and argues that at key moments in the formation of digital capitalism, the terms helped create a field of action where management communities could envision, discuss, and coordinate, in a safely depoliticised way, the fact that markets and property are not natural, that social and political choices are necessary to create markets and property out of human relations that are not self-evidently things. Analysing the terms, not as ideologies, but as what Raymond Williams called “social experiences in solution”, the essay focuses on the terms’ emergence before the regimes of accumulation with which they are now associated. This analysis suggests that close attention to language in historical context can help illuminate the emergence of political economic changes, showing that the rise of digital capitalism can be seen as, at the outset, as an effect, as much as a cause, of particular structures of feeling. It also suggests that scholars of current trends should not take for granted current buzzwords, but should treat their use and definition as sites of struggle.